Influence of cutting-edge tip geometry on the tool–workpiece electrical contact resistance - Murata, M. (Advances in production engineering and management, 2025)
It is well established that the electrical resistance generated at the contact interface between dissimilar metals is strongly correlated with the actual contact area. By leveraging this phenomenon in cutting operations, we have successfully achieved in-process identification of flank wear width during machining. The method has shown particularly favourable performance under finishing conditions involving interrupted cutting, where tool monitoring is generally considered challenging. However, cutting operations employ a wide range of tool geometries, cutting parameters, and machining configurations, and it remains unclear whether the proposed approach is universally applicable across these variations. To address this issue, the present study focuses on turning, a process in which the tool–workpiece contact time is relatively long, and investigates the applicability of the method to diverse cutting geometries. Specifically, we examine how differences in tool geometry and the chip–rake-face contact area influence the electrical contact resistance between the tool and the workpiece. The results indicate that, for unused tools, variations in nose radius do not affect the electrical contact resistance measured at the tool–workpiece interface. In contrast, the contact between the flowing chip and the rake face is strongly dependent on rake angle. Consequently, for tools with negative rake angles, chip–rake-face interaction was found to have a pronounced influence on the electrical contact resistance at the tool–workpiece interface.
Keywords: contact resistance; in-process monitoring; kontaktni upor; nagibni kot; nose radius; rake angle; real time evaluation; tool wear detection; zaznavanje obrabe orodja